Portomesenteric Venous System Gas after CT Colonography: A Case Report - Ilaria Sansoni; Claudia Lucia Piccolo; Ilenia Di Giampietro; Matteo Polacco; Bruno Beomonte Zobel (Case Reports in Radiology)
Portomesenteric vein gas can occur owing to a variety of interraleted factors such as loss of mucosal integrity and intraluminal overpressure, and the most common and serious cause is bowel ischemia, which requires urgent laparotomy. Nevertheless, when portal venous gas is caused by nonischemic causes, surgery is not required and it can be treated conservatively. So, its features should be carefully evaluated at CT scan, together with clinical findings. The authors report a case of an old male with portomesenteric venous system gas after CT colonography, without evidence of pneumatosis intestinalis or colonic perforation. A CT scan without enema was required after 24 hours in absence of worsened patient conditions, revealing the disappearance of gas in mesenteric vein and in the portal venous system.